HUBUNGAN PERILAKU ASERTIF DENGAN PENYESUAIAN DIRI ANAK USIA 4-5 TAHUN DI PAUD HARAPAN BUNDA DESA AIR PANAS KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Siti Aliyah; Ria Novianti; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this study was to determine the relationship of assertive behavior with self-adjustment of children aged 4-5 years in PAUD Harapan Bunda Air Panas Village district Pendalian IV Koto Rokan Hulu regency. This study was quantitative study with correlation study type. Sampling technique used in this study is a sample saturated with a total sample of 34 children. The data collection techniques were used observation sheets. The data analysis techniques were used Pearson Product Moment Correlation Coefficient. The results of this study indicate that the correlation coefficient of assertive behavior with adjustment is 0.478 with a significance value of 0.004 (p <0.005). Indicates that there is a positive relationship or correlation. This means that if a person has high assertive behavior, the adjustment of the person is also higher. This positive and significant relationship shows that there is a good interest between assertive behavior and self-adjustment. In categorizing correlations, the correlation coefficient is included in the category of medium correlation.Keywords: Assertive Behavior, Self-Adjustment